2014
DOI: 10.1111/jam.12590
|View full text |Cite
|
Sign up to set email alerts
|

Management of Meloidogyne incognita on tomato with endophytic bacteria and fresh residue of Wasabia japonica

Abstract: This study provides novel way for disease management using combination of endophyte and host residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The main virulence factors of these bacteria are lipopolysaccharides (O‐antigen), polysaccharide capsules (K‐antigen), adhesins (fimbriae class 1 and class 3), siderophores (enterobactin and aerobactin), tetrodotoxin, different hydrolytic enzymes, bacteriocins, such as raoultellin L Raoultella isolates are also able to form biofilms. It has been shown that processing crops, particularly tomatoes, with a suspension of R. terrigena have antiparasitic activity and can be used in agricultural biotechnology 16 . Raoultella terrigena could be isolated from the intestine of pufferfish, 17 milk 18 and may be used in biotechnology as 2,3‐Butanediol produser 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main virulence factors of these bacteria are lipopolysaccharides (O‐antigen), polysaccharide capsules (K‐antigen), adhesins (fimbriae class 1 and class 3), siderophores (enterobactin and aerobactin), tetrodotoxin, different hydrolytic enzymes, bacteriocins, such as raoultellin L Raoultella isolates are also able to form biofilms. It has been shown that processing crops, particularly tomatoes, with a suspension of R. terrigena have antiparasitic activity and can be used in agricultural biotechnology 16 . Raoultella terrigena could be isolated from the intestine of pufferfish, 17 milk 18 and may be used in biotechnology as 2,3‐Butanediol produser 19 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that processing crops, particularly tomatoes, with a suspension of R. terrigena have antiparasitic activity and can be used in agricultural biotechnology. 16 Raoultella terrigena could be isolated from the intestine of pufferfish, 17 milk 18 and may be used in biotechnology as 2,3-Butanediol produser. 19 Raoultella terrigena are gram-negative nonmotile capsule forming bacteria belonging to the Enterobacteriaceae family.…”
Section: Raoultella Terrigena Short Overviewmentioning
confidence: 99%
“…The roots were shaken gently to remove the soils that were not tightly attached, and the rhizosphere soils were collected by using a brush to separate the soils from the root system. In order to obtain endophytic bacteria, the collected roots were washed under slow-running tap water to remove adhering soil particles, followed by surface sterilization with NaClO (1%, Tianjin Best Chemical) for 5 min, successively rinsed five times with sterile distilled water, and then dried with sterile filter paper for root-endophyte isolation ( Li et al, 2014 ). Five replicate soil and four replicate root samples from infested and non-infested plants per location were collected, with five individual samples for each replicate.…”
Section: Methodsmentioning
confidence: 99%
“…Zakaria et al [52], Li et al [53], Wang et al [54], Garcia-Raya and Michel [55], Jin et al [56] reported that integrating biofumigation with antagonistic endophytic bacteria controls SBPs by regulating soil bacterial community structure and that the combined application of these microorganisms and biofumigation had superior efficacy against the SBPs compared with each treatment alone.…”
Section: Biofumigation and Antagonistic Microorganismsmentioning
confidence: 99%